(untitled) (Research, Society and Development, 2021)
Playing a musical instrument may benefit the individual’s skill in activities not linked to music. Current literature suggests that executive functions (EFs), especially inhibitory control, may be responsible for this phenomenon. However, evidence is still mixed. Maybe due to the interference of other variables, not accounted for by the studies design. This research was conducted with teenager musicians with neurotypical development, and used the five digits test (FDT). This test is within the Stroop paradigm, which is often used in researches dealing with EFs and music, and is able to measure inhibitory control. The FDT has the advantage, however, of a greater sensibility regarding the task’s difficulty (which is incremental) and temporal development (if mistakes are made in the first of the final half). Thus, it can account for variables still not studied. This was a transversal study conducted with 40 teenagers (ages 14 – 17, M = 15.4 SD = .9, Median = 15) from a private school in Curitiba, Brazil. 20 of whom were musicians (played at least one instrument) and 20 were non-musicians. The results showed that there is no difference in their performance in simpler tasks, which use automatic processes only. Musicians have, however, a better performance in more complex tasks, which require more from conscious cognitive control. This variable may be important in explaining the discrepancy in literature, as well as guiding future research.